Features of building virtual PBX - Tokar, L.O. (Radiotekhnika, 2022)
The article considers the features of organizing highly efficient telephone communication using cloud-based PBXs. The advantages of solutions based on IP-telephony compared to classical automatic telephone exchanges are treated. It is shown that the use of a virtual PBX as a separate configuration of a dedicated server will provide a flexible system of settings. The virtualization model is considered. The analysis of virtualization methods is carried out and it is noted that the result of their development is the emergence of multi-core processors, an increase in the throughput of computer interfaces, an increase in the capacity and speed of data storage systems. It is shown that each of these methods differs in hardware emulation methods and finds its place depending on the application. A solution using the Asterisk software product is considered for organizing the IP-telephony. The configuration of the virtualization environment setting is discussed. It is proposed to use a reliable PROXMOX VE infrastructure, which is an open source virtualization system and support for live migration. Studies have been carried out to determine the performance parameters of virtualization technologies, namely, hypervisor and container ones. It is noted that the main peak of the load on the OP is the assembly of the system from binary files, which requires significantly more resources (the load increases by about 2 times) than the preparation of these files. During the CPU load analysis, the virtual machine was found to be very demanding. It has been proven that virtual machines with hypervisor virtualization technology consume more server hardware resources than virtual machines with container virtualization technology.